Before and after Avicenna : proceedings of the First Conference of the Avicenna Study Group - Reisman, David C.; Al-Rahim, Ahmed H. (Islamic philosophy, theology, and science ;, 2003)
This volume contains the proceedings of the first meeting of the Avicenna Study Group. Each of the papers presents the most recent research conclusions in its respective topic. These conclusions include new insights into Avicenna's revision of Aristotle and Plotinus, specific areas of his theories of psychology and metaphysics, his intellectual interaction with the theologians of his period, the historical and social context in which Avicenna worked, the reception of his thought among Syriac-writing authors, among later Ishraqi philosophers, and in Shi'ite peripatetic philosophy. These insi.